Fabrication of Air Freshening Spongy Three Dimensional Electrospun Membrane - Mulmi, Purnima; Pant, Hem Raj (Journal of the Institute of Engineering, 2018)
In this work, air freshening spongey 3D nanofibrous membrane of nylon-6 (N6) is fabricated via electrospinning process. Viscous N6 solution dissolved in formic acid/acetic acid solvent system was allowed for electrospinning to obtain 2D membrane. As-fabricated 2D membrane is converted into 3D one by using gas foaming technique. Lemon grass essential oil as a fragrance was incorporated through 2D and 3D porous membrane by evaporating essential oil at 60°C for 5 hours. The morphology of different membranes was examined from FE-SEM images which showed that 3D membrane is far porous than 2D one. The control fragrance release from the 3D spongy membrane was evaluated from the weight loss of oil-loaded membrane for 60 days which showed that the 3D membrane had more oil uptake and the controlled release of oil over the studied time. FT-IR spectra of oil-incorporated 3D membrane at different interval of times indicated the presence of fragrance even after the 60 days. The result showed that as-fabricated sponge 3D membrane may be a potential candidate for the future air freshening materials. Journal of the Institute of Engineering, 2018, 14(1): 14-21